If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -6 = -15 Reorder the terms: -6 + c = -15 Solving -6 + c = -15 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + c = -15 + 6 Combine like terms: -6 + 6 = 0 0 + c = -15 + 6 c = -15 + 6 Combine like terms: -15 + 6 = -9 c = -9 Simplifying c = -9
| (3x^2+6xy)dx+(2x^2+3xy)dy=0 | | 7+10x=7+x | | 2j+20=2 | | 87=64+x | | x-18=90 | | x+15=48 | | 7-xi=x+y+2i | | 4x+3y-78=0 | | 6x^2-225x=37.5 | | 4*(x-97)=68 | | 5[-y+1]=-8 | | -3x^2-9x+15=0 | | y+2x-10=0 | | 3(x-4)+5=25 | | 4(x-2)+8(x-4)=8 | | 5p(p+2)=0 | | x-2y+10=0 | | 158x+5947=6 | | xy=13599273702913 | | 5(7-x)=-5 | | (2k-1)x^2+2kx-k=0 | | 2ln(2x-1)-10=0 | | 9-4x=9+3x | | 2f+1=3f-1.5 | | 2b+7=5b-2 | | 35y+1=56 | | 7[25-m]-2m=2[3m-25] | | y=1.5x+7.7 | | -5u-20=3(u-4) | | -2(u+3)=6u+10 | | 0=1829x-3 | | 8y+22=-2(y+9) |